Meningkatkan Kemampuan Pemahaman Konsep Matematika Siswa SMP Melalui Model Pembelajaran Think Pairs Share Pada Materi Lingkaran (Universitas Muhammadiyah Palembang, 2023)
The ability of students to understand mathematical concepts is very important, because when students understand mathematical concepts, students can apply and use these concepts to further abilities, for example students can analyze a problem after understanding the concept. If students do not master the concept, it is certain that students cannot continue material that requires abilities beyond the ability to understand concepts. One technique in learning mathematics to improve students' ability to understand mathematical concepts is to use the Think Pairs Share (TPS) learning model developed by Frank Lyman Laura. The Think Pairs Share (TPS) learning model is one of the cooperative learning models. Learning with the TPS method is learning that stimulates student activity to think and discuss the results of their thoughts with their groups and also stimulates students' courage to express their opinions in front of the class. In addition, it can encourage and provide opportunities for students to restate opinions or ideas, listen to other groups, and respond appropriately to the opinions of other groups. The atmosphere generated will be more enjoyable because students learn and exchange ideas with peers so as to improve students' ability to understand mathematical concepts.